PENGARUH MEDIA PEMBELAJARAN MONALISA (MONOPOLI PANCASILA TERHADAP KARAKTER KEWARGANEGARAAN SISWA KELAS X TPM DI SMK NEGERI 1 DRIYOREJO - Sonya Riri Safitri; Siti Maizul Habibah Sitihabibah; Listyaningsih listyaningsih; Rianda Usmi Riandausmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low level of civic character among students in Pancasila Education lessons. One strategy to address this issue is the use of an innovative and engaging instructional tool known as "Monalisa" (Pancasila Monopoly). The study aimed to determine the impact of using the Monalisa learning medium on the civic character of Grade X TPM students at SMK Negeri 1 Driyorejo. A quantitative approach was employed using a quasi-experimental design specifically, the Non-equivalent Control Group Design. The study population consisted of Grade X TPM students: class X TPM 2 37 students served as the control group using the Domino Game medium, and class X TPM 3 36 students served as the experimental group using the Pancasila Monopoly medium. Data were collected using a civic character questionnaire. Data analysis involved normality tests, homogeneity tests, descriptive statistics, and hypothesis testing via a paired-sample t-test using SPSS. The results indicate that the use of the Monalisa (Pancasila Monopoly) medium significantly influenced students' civic character, evidenced by a significance value of 0.000 (< 0.05) and an increase in the mean score from 44.00 to 49.31.